“That Which I Am…”: Notes from the Personal Library of Director Juozas Miltinis - Mikelinskaitė, Angelė (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English]Based on the personal library of director Juozas Miltinis (1907–1994), this article studies the marginal notes of the library’s books: information notes, texts, signs and tags, focusing on the marginal remarks that emerged as the expression of the library owner’s work with the books. The relationship between these marginals and the contents of the books is explained. The content, functional nature and meaning of marginalia are discussed. This article gives an overview of what these supporting informational entries behind the book’s main text testify.By exploring the marginal records of the director’s personal library, the author of this article searches for the interface with the personality’s activity and the personality’s relationship with environment.